IMPLEMENTASI SARANA DAN PRASARANA PENJASORKES TERHADAP 7 KOMPONEN DASAR PENJASORKES - PRAYOGI, TATAG (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Implementation of national development in the field of education is an attempt to educate the nation in order to improve the quality of the Indonesian people and realize that advanced humans, fair and prosperous. To achieve national goals in education and the government's efforts to extend equal opportunity to obtain a high quality education for all Indonesian people towards the creation of high quality Indonesian man with a mean increase in the education budget. Implementation of physical education teaching and learning activities and sports ( Penjasorkes ) can not be separated from the availability of infrastructure in the school. In this study discusses the availability of facilities and infrastructure Penjasorkes and utilization of facilities and infrastructure by teacher educators who refers to the 7 basic components Penjasorkes. In the study done at a public school district Lumajang , found the following results : (1). SMA Negeri 1 Lumajang scored 180, (2) SMA Negeri 2 Lumajang got a score of 150, (3) SMA Negeri 3 Lumajang scored 190. From the results of the study can be taken average state facilities and infrastructures in Lumajang district is 173 in the category "B" (good). The state of infrastructure Penjasorkes for high schools in the District Lumajang is good (B) with a value of 173. It can be concluded that the real state of infrastructure in SMA Penjasorkes District of Lumajang has good se. But inversely proportional to the availability of good infrastructure, was a teacher teaching a class XI Penjasorkes can not maximize the available infrastructure such Keywords: Facilities and infrastructure, 7 Penjasorkes Basic Component, districts lumajang